Bibliometric analysis of research on public administration reform (Journal of Economic Research & Business Administration, 2024)
This article complements the initial studies based on bibliometric analysis. The relevance of bibliometric analysis is the study of a large amount of data in scientific research. The purpose of the study is to conduct a bibliometric analysis to determine the state of research toward reforming public administration and future areas of research and mapping.In our research strategy, 151 articles were selected on the reforms carried out in the civil service in 1991-2023. With VOSviewer software, bibliometric networks were created and visualized. The bibliometric analysis of the study used the Scopus academic base to reform the public administration system. The conclusions of these studies were drawn and presented in this article providing an opportunity for further understanding of the systematic development of the study.The success of the study informed the dynamics of research development in the public administration system. The best articles, publications, and studies of the most cited authors and organizations on the management of the state system are identified, and they contribute to the scientific literature, describing its current state.In studies using bibliometric analysis, elements of transparency and productivity have been identified that can be used in public administration and e-government reforms. In addition, the study demonstrated the experience of developing public system management reforms in peer-reviewed publications around the world. In Kazakhstan, these studies have been intensively conducted since 2020, while in developed countries such as the United States and the United Kingdom, a high rate of use has been observed since 2010.Key words: Kazakhstan, public administration reforms, VOSviewer, bibliometric analysis, literature review, scientific mapping, analysis of joint words.